(untitled) (Human Computation, 2015)
The dynamic nature of crowdsourcing platforms poses interesting problems for users who wish to schedule large batches of tasks on these platforms. Of particular interest is that of scheduling the right number of tasks with the right price at the right time, in order to achieve the best performance with respect to accuracy and completion time. Research results, however, have shown that the performance exhibited by online platforms are both dynamic and largely unpredictable. This is primarily attributed to the fact that, unlike a traditional organizational workforce, a crowd platform is inherently composed of a dynamic set of workers with varying performance characteristics. Thus, any effort to optimize the performance needs to be complemented by a deep understanding and robust techniques to model the behaviour of the underlying platform(s). To this end, the research in this paper studies the above interrelated facets of crowdsourcing in two parts. The first part comprises the aspects of manual and automated statistical modeling of the crowd-workers’ performance; the second part deals with optimization via intelligent scheduling over multiple platforms. %based on simulation testbed generated by the statistical models.Detailed experimentation with competing techniques, under varying operating conditions, validate the efficacy of our proposed algorithms while posting tasks either on a single crowd platform or multiple platforms. Our research has led to the development of a platform recommendation tool that is now being used by a large enterprise for performance optimization of voluminous crowd tasks.